Ofício do assistente substituto do magistrado do distrito de Xiangshan, Dai, ao procurador de Macau, sobre o litígio relacionado com um português, residente em Macau, que construiu ilegalmente um muro na Praia do Manduco (1775)
This archival document is an imperial edict issued on 12 June 1739 (11th day of the 5th month, 4th year of the Qianlong reign) by the Acting Magistrate of Chashan County, Magistrate Dai, under authority of the Maritime Defence and Civil-Military Prefectural Administration (Hai Fang Jun Min Fu) of Guangdong province. It addresses the unlawful construction of stone foundations for a water fortress (*Shui Cheng*) by the foreign resident *Ai-ai-zhu* at Chan Chu Shi (Toad Rock), a coastal promontory near Macau. The edict commands the Qing-appointed foreign headman (*Yi Mu*) to supervise *Ai-ai-zhu* in the immediate demolition and relocation of all newly laid foundations away from the site, and to submit a formally sealed compliance report (*Zun Yi Bao Fu*) without delay. The text records prior inspections, repeated admonitions, an official dispatch (*Xi*), and escalating administrative pressure due to non-compliance, culminating in a reissued urgent order threatening formal legal enforcement (*Tong Piao*). Key figures include Magistrate Dai, Prefect Kong of the Hai Fang Jun Min Fu, *Ai-ai-zhu*, and the *Yi Mu*. The document reflects Qing bureaucratic procedures for regulating foreign residents in the Macau–Guangdong maritime frontier, evidencing jurisdictional tensions, delegated authority, and enforcement mechanisms within mid-Qing coastal administration.
Keywords: Ai-ai-zhu; Chashan County Magistracy; Hai Fang Jun Min Fu; Qianlong Reign Edict; Qing local governance; Shui Cheng construction; Toad Rock; Transcription; Yi Mu; coastal fortification regulation; maritime defence jurisdiction; stone foundations demolition